Technology, creativity and the media in engineering China’s future - Sullivan, Jonathan (SAGE Publications, 2014)
Political, economic and intellectual elites in China have for some time been in the grip of ‘futurology’ as they reflect on thirty years’ of extraordinary economic development and ask ‘what next’? China has a dream, in fact it has many visions of what it may become, reflecting robust debate and competition to define the nation’s future course of reform and development (Callahan, 2013). On assuming the top party and state positions in October 2012 Xi Jinping quickly unveiled the China Dream (Zhonguomeng) as the maxim for his leadership. Although specification of what the dream will entail is yet to be fully explicated, one thing is certain: low-cost production and outsourcing more advanced economies’ dirty jobs is neither the subject of China’s dream nor is it any longer considered the means to delivering it. The ‘world’s factory’ model that facilitated China’s remarkable economic growth has come under pressure from all sides, as the party acknowledges its unsustainability and people deal with the consequences. Party elites and policymakers have taken significant steps toward a different and more sustainable model to secure long term growth and it is hoped that low-end manufacturing will give way to a service based economy and consumer culture facilitated by urbanization, migration and developing greater creative capacity. These plans are underpinned by the ambition to become an ‘innovative nation’ (chuangxinxing de guojia), to develop soft power resources to go with economic might, and to raise the ‘quality’ (suzhi) of the people. As the three books covered in this review essay demonstrate, technology, culture and the media are closely implicated, and closely controlled, in the Chinese state’s quest for development.